Plasmonic Nanotweezers and Nanosensors for Point‐of‐Care Applications. Issue 13 (17th April 2021) - Peng, Xiaolei; Kotnala, Abhay; Rajeeva, Bharath Bangalore; Wang, Mingsong; Yao, Kan; Bhatt, Neel; Penley, Daniel; Zheng, Yuebing
Abstract: The capabilities of manipulating and analyzing biological cells, bacteria, viruses, deoxyribonucleic acids (DNAs), and proteins at high resolution are significant in understanding biology and enabling early disease diagnosis. The progress in developments and applications of plasmonic nanotweezers and nanosensors is discussed, where the plasmon‐enhanced light‐matter interactions at the nanoscale improve the optical manipulation and analysis of biological objects. Selected examples are presented to illustrate their design and working principles. In the context of plasmofluidics, which merges plasmonics and fluidics, the integration of plasmonic nanotweezers and nanosensors with microfluidic systems for point‐of‐care (POC) applications is envisioned. Perspectives on the challenges and opportunities in further developing and applying the plasmofluidic POC devices are provided. Abstract : In this Review, progress in plasmonic nanotweezers and nanosensors is discussed, and examples to illustrate their design, working principles and applications are presented. Perspectives on the opportunities and challenges associated with the integration of plasmonic nanotweezers and nanosensors with microfluidic systems for point‐of‐care applications are also provided.